Bioaccumulation of iron (Fe) and lead (Pb) in various body tissues of Telescopium telescopium in Peninsular Malaysia: Implications for biomonitoring and sustainability - Chee Kong Yap; Khalid Awadh Al-Mutairi (Journal of Fisheries, 2024)
Heavy metal contamination in marine environments poses a significant threat to aquatic ecosystems and human health. This study investigates the accumulation patterns of iron (Fe) and lead (Pb) in seven different body tissues (cephalic tentacle [CT], digestive caecum, foot, gill, mantle, muscle, and remaining soft tissues) of Telescopium telescopium collected from Peninsular Malaysia. Using heat map visualization and correlation analysis, we examined the relationships between Fe and Pb levels in various body tissues. High positive correlations were observed in Fe levels between the foot- CT (r = 0.86), and Pb levels between the muscle and CT (r = 0.95). Factor analysis highlighted the complex interplay of environmental and physiological factors influencing metal accumulation. Our findings underscore the importance of considering multiple tissues for accurate biomonitoring of metal pollution in marine environments, particularly in the context of sustainability and, environment, social and governance considerations.